2022
DOI: 10.17323/2312-5942-2022-12-2-183-197
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of job satisfaction and work engagement in the relationship between self-reported person-job fit and job performance

Abstract: Purpose. Identifying the right people for the right jobs is crucial to maximizing employees’ job performance. Although the literature has consistently found a positive relationship between person-job-fit (P-J fit) and job performance, little attention has been given to the underlying mechanisms of the relationship. The present study proposed a parallel mediation model to investigate the hypothetical mediating roles of job satisfaction and work engagement in the relationship between self-reported P-J fit and jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Even though universal theory supports the relationship between PJ fit and PO fit to employee engagement and employee engagement to intention to quit, the mediation process is only promoted by one type of industry, such as hospitality (Saleem et al, 2021). Other studies show different results like person-job fit had not influenced employee engagement (Lee et al, 2022;Bui et al, 2017), PO fit had a partial impact on employee engagement (Aydemi̇r & Endi̇rli̇k, 2023). Furthermore, Salem et al (2021) explain that the person-job fit and the PO fit relate to employee engagement and lead to the intention to quit.…”
Section: Introductionmentioning
confidence: 93%
“…Even though universal theory supports the relationship between PJ fit and PO fit to employee engagement and employee engagement to intention to quit, the mediation process is only promoted by one type of industry, such as hospitality (Saleem et al, 2021). Other studies show different results like person-job fit had not influenced employee engagement (Lee et al, 2022;Bui et al, 2017), PO fit had a partial impact on employee engagement (Aydemi̇r & Endi̇rli̇k, 2023). Furthermore, Salem et al (2021) explain that the person-job fit and the PO fit relate to employee engagement and lead to the intention to quit.…”
Section: Introductionmentioning
confidence: 93%
“…Prior studies found that managers' ethical leadership plays an important role in influencing employees' psychology and well-being in the workplace (Dust et al, 2018;Fu et al, 2020). Other scholars argue ethical leadership has a strong correlation to employees' job satisfaction and job engagement (Lee et al, 2022;Neale, 2020;Wang, Hsieh, 2012). It also has positively affected workers ' organizational commitment (Gallego-Alvarez et al, 2020;Jha, Singh, 2019;Limpo, Junaidi, 2022;Ölçer, Coşkun, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies also examined the correlation between ethics and job satisfaction in an organizational context (Koh, Boo, 2001;Lee et al, 2022). The authors concluded that Malaysia and Singapore's company leadership styles positively influence the work environment and ethical principles in the workplace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation